2005
DOI: 10.1038/sj.gene.6364176
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gene organization in the human IGHV region on single chromosomes

Abstract: Organization of the IGHV genes (n ¼ 108) on single human chromosomes has been determined by detecting these sequences in single sperm using multiplex PCR amplification followed by microarray detection. A total of 374 single sperm samples from five Caucasian males were studied. Three deletion/insertion polymorphisms (Del I-Del III) with deletion allele frequencies ranging from 0.1 to 0.3 were identified. Del I is a previously reported polymorphism affecting three IGHV genes (IGHV1-8, IGHV3-9, and IGHV2-10). Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 47 publications
8
29
0
Order By: Relevance
“…64 Importantly, four of these five germline IGHV genes contributing to these antibodies are known to vary in copy number. 33,38,40,41,51,52 Taken together, such observations provide a potential example for which complete descriptions of IGHV gene allelic and genomic structural variation may prove essential for understanding infectious disease susceptibility, and useful in the administration of vaccines aimed at eliciting specific antibodies.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…64 Importantly, four of these five germline IGHV genes contributing to these antibodies are known to vary in copy number. 33,38,40,41,51,52 Taken together, such observations provide a potential example for which complete descriptions of IGHV gene allelic and genomic structural variation may prove essential for understanding infectious disease susceptibility, and useful in the administration of vaccines aimed at eliciting specific antibodies.…”
mentioning
confidence: 99%
“…There are several examples of homozygous deletions containing functional IGHV genes (Table 1). 28,33,38,39,51,52 In addition, an analysis of naive B-cell IGHV gene repertoires using next-generation 454 sequencing revealed that 15 of the 56 IGHV genes described from these repertoires were observed in only a subset of the 12 individuals screened. 6 Seven of these fifteen genes were previously reported to occur in insertion/deletion polymorphisms, and thus these observed 'holes' in the naive repertoire are likely due to homozygous deletions.…”
mentioning
confidence: 99%
See 3 more Smart Citations